Esperança cristã : uma ética para a vida a partir da teologia de Jürgen Moltmann - Mattiello, Giovani Adelino (2014)
Dissertation presented for the Master`s Degree in Theology about the Christian hope as an ethic that is able to resignify and orient life, from the thought of the theologian Jürgen Moltmann. A modern technical scientific society is characterized based on its crises. The modernity in crisis of feelings and values and its consequences in the social behavior is analyzed. This model of society and its conceptions about individual, society, life, death, nature, religion and culture is criticized. It is sought through Moltmann theology to comprehend the ethic of hope as an alternative for the overcoming of this reality of crisis. The Christ resurrection is said as a sign of hope of the humanity, and the Christ Gospel as a model and criterion for human relations. An ethic of hope is proposed to redefine the humanity place in front of God and the creation, motivating to a more active participation for the seeking of a full life with dignity and justice.